GASTRONOMIC TRADITIONS OF ANCESTRAL ORIGIN IN THE CUNDIBOYACENSE HIGHLANDS, COLOMBIA - Pérez, Juan Manuel Montes (2023)
The Cundiboyacense highlands, known as an important agricultural producer that guarantees food security for several departments of the country, was the settlement of the Muisca indigenous community. The muiscas bequeathed a gastronomic heritage materializing knowledge, techniques, and ancestral knowledge derived from gastronomic preparations and traditional cuisine transmitted orally. Nowadays, these gastronomic manifestations are threatened because they are not documented and recognized as a symbolic value which contributes to their maintenance and dissemination. In this light, this study aims to learn about the techniques and knowledge associated with the ancestral gastronomy of indigenous origin in the Cundiboyacense highlands of Colombia. The research methodology was structured on the basis of the qualitative approach, and the ethnographic method. The techniques used were observation and semi-structured interviews. The information was systematized and analyzed using the Atlas.ti qualitative analysis software. The results show that ancestral gastronomy and its traditional cuisines constitute a fundamental cultural heritage that determines the identity of the territories. It also coheres and interweaves the memory and social imaginaries as vehicles of cultural approach that should be maintained, disseminated, and recreated.